The Effect of Financial and Non-Financial Information on Underpricing in Initial Public Offerings - Oktananda, M. Reza; Gantyowati, Evi (Journal of Asian Multicultural Research for Economy and Management Study, 2023)
This study aims to examine the financial and non-financial information factors that affect underpricing in companies conducting IPOs in 2020 - 2022. The data analysis technique in this study consists of classical assumption tests and hypothesis testing using multiple linear regression analysis methods. The test results show that the debt-equity ratio does not affect underpricing. In contrast, earnings per share has a positive effect on underpricing, and underwriter reputation and auditor reputation have a negative effect on underpricing.